Development of adjuvanted HIV vaccines tailored for early life: immunologic rationale, clinical experience, and future directions - Kinga K. Smolen; Kristina De Paris; Asimenia Angelidou; Troy M. Martin; Simon D. van Haren; Ofer Levy (Current Opinion in HIV and AIDS, 2026)
Purpose of review This review highlights the rationale for and clinical experience in advancing age-specific adjuvantation systems to develop well tolerated and effective pediatric HIV vaccines. Recent findings Due to both cellular and soluble factors, infant immunity is distinct from that of older children and adults, featuring Th2 bias, tolerogenic APC programming, and reduced Tfh support. Due to distinct functional responses downstream of pattern recognition receptor signaling, adjuvant action is age-specific. Despite a growing pipeline of adjuvants and increasing interest in developing early-life immunization strategies against HIV, few adjuvants have been rigorously evaluated for use in pediatric HIV vaccines. In line with FDA Modernization Act 2.0, systems vaccinology and age-specific immunoprofiling in vivo and in vitro can inform down selection and optimization of age-specific adjuvanted HIV vaccine formulations. Several adjuvants have been assessed as components of HIV vaccines in infants including Alum, the oil-in-water emulsion MF59 and the TLR4 agonist glucopyranosyl lipid A (GLA). Summary There is strong rationale to develop an infant HIV vaccine to provide early-life protection, and several adjuvants have been assessed thus far in early-phase clinical studies. With a growing adjuvant pipeline, much work remains to assess which adjuvants should be advanced for an infant HIV vaccine. Leveraging age-specific preclinical studies including immune profiling and human in-vitro modeling can inform down selection to identify adjuvantation systems offering safety and antigen dose sparing, while enhancing breadth and durability of vaccine immunogenicity.